Community-Based Inclusive Education for the Rights and Welfare of Students with Disabilities in Malang City - Juli Astutik; Eko Rizki Purwo Widodo; Zaenal Abidin (WISE Pendidikan Indonesia, 2026)
This study develops a community-based inclusive education model to strengthen the educational rights and social welfare of students with disabilities in Malang City, Indonesia. A qualitative multi-site descriptive design was employed across five special schools. Data were generated through classroom observations, semi-structured interviews with five principals and five teachers, document analysis, and a focus group discussion, then analysed using the interactive procedures of data condensation, display, and conclusion drawing. The findings show that community-based inclusion is enacted through five mutually reinforcing components: adaptive use of the national curriculum; curriculum modification and differentiated instruction according to learners’ functional profiles; flexible grouping and visual-demonstrative learning strategies; individualized assessment through Individualized Education Programs, progress records, and tailored worksheets; and structured collaboration among schools, parents, community organizations, and local support networks. These components form a rights-based ecosystem that expands access, participation, learning continuity, and social acceptance beyond the classroom. The proposed model positions community participation not as supplementary assistance but as an institutional resource for responsive educational services and student wellbeing. It offers an actionable framework for strengthening inclusive education and locally grounded social-welfare policy, while contributing to SDG 4 and SDG 10.